Black TiO(2) Synthesis by Chemical Reduction Methods for Photocatalysis Applications - Andronic, Luminita (Front Chem, 2020)
Applications of TiO(2) nanomaterials in photocatalysis, batteries, supercapacitors and solar cells, have seen widespread development in recent decades. Nowadays, black TiO(2) have won attention due to enhancing the solar light absorption by the formation of oxygen vacancies and Ti(3+) defects, to promote the separation of photo-generated charge carriers leading to the improvement of the photocatalytic performance in H(2) production and pollutants degradation. The enhanced photocatalytic activity of black TiO(2) is also due to a lattice disorder on the surface and the presence of oxygen vacancies, Ti(3+) ions, Ti-OH and Ti-H groups. Enhancing the optical absorption characteristics of TiO(2) and change of energy level and band-gap of materials have been successfully demonstrated to improve their photocatalytic activities, especially for black TiO(2) nanoparticles, which promote visible light absorption. The current review focuses on the investigation of the chemical reduction synthetic route for black TiO(2) nanomaterials, and their proposed association with green applications such as photodegradation of organic pollutants and photocatalytic water splitting. The synthesis methods of black TiO(2) involves the changes from Ti(4+) to Ti(3+) state, into different strategies: (1) The use of highly active hydrogen species such as H(2), H(2)/Ar or H(2)/N(2) gases, and metal hydrides (NaBH(4), CaH(2)), (2) the reduction by active metals such as aluminum, magnesium and zinc, and (3) organic molecules such as imidazole and ascorbic acid.